ESTIMATION OF ABOVEGROUND FOREST BIOMASS AND CARBON STORAGE OF BANGLADESH - Ajoy Mojumder; Md Sahadat Hossain; Timothy A Volk (BIOTROPIA, 2023)
Forest biomass helps mitigate climate change impacts through sequestration of atmospheric carbon dioxide and potentially storing it for long periods of time. Deforestation and timber harvesting cause the reduction of forest biomass resulting in the reduced carbon sequestration capacity and alterednatural balance of forest ecosystems. We used remote sensing and GIS tools in the four important forest cover zones within five districts of Bangladesh to compare the aboveground forest biomass (AGB) changes between 2014 and 2020. We found an increased AGB in Sundarban mangrove forest from 89.73 Mg.h-1 in 2014 to 90.76 Mg.h-1 in 2020. Similarly, the AGB was found to be increased for Ukhiya hill forest from 7.89 Mg.h-1 in 2014 to 8.89 Mg.h-1 in 2020. Contrary, the average AGB content in Nijhum Dwip mangrove forest decreased from 44.36 Mg.h-1 in 2014 to 37.46 Mg.h-1 in 2020. The average AGB of Modhupur decidious forest also found to be decreased from 110.01 Mg.h-1 in 2014 to 107.22 Mg.h-1 in 2020. The decreased biomass contents could be attributed to anthropgenic factors as indicated by the presence of human activities and this informatin will be helpful for forest restoration and management in Bangladesh.